Revealing the Flexible 1D Primary and Globular Secondary Structures of Sulfur‐Rich Amorphous Transition Metal Polysulfides. Issue 12 (17th October 2019) - Artemkina, Sofya B.; Enyashin, Andrey N.; Poltarak, Anastassiia A.; Fedorenko, Anastasiya D.; Makarova, Anna A.; Poltarak, Pavel A.; Shin, Eon‐Ji; Hwang, Seong‐Ju; Kim, Sung‐Jin; Grayfer, Ekaterina D.; Fedorov, Vladimir E.
Abstract: Sulfur‐rich transition metal polysulfides MS5 (M=Mo, W) are synthesized by a low‐temperature solution method from corresponding carbonyls M(CO)6 and elemental sulfur. Extensive characterization reveals that all sulfur atoms are assembled into disulfide ligands (S−S) within the structure of the amorphous spherical particles. Their thermodynamic stabilities are estimated for the first time using density functional theory (DFT) calculations, indicating two stable chain models composed either of binuclear [M2 S8 ] or trinuclear [M3 S12 ] fragments linked through S−S units. Molecular dynamics (MD) DFTB simulation proves that the S−S bridges predetermine the supreme flexibility of the polysulfide chains as primary structures of MS5 and their globular secondary arrangements. Interestingly, this type of structural organization is reminiscent of that for classical polymers. Thus, the reasons for MS5 forming exclusively as amorphous phases are uncovered, which may be extended to many other sulfur‐rich polysulfides. The potential of these materials as increased capacity cathodes for lithium‐ion batteries is shown. Abstract : Exclusively amorphous nature of MoS5 and WS5 is shown to be related to flexible chains in their structures, akin to traditional polymers, making these materials remarkably different from most of the other transition metal chalcogenides, which may be obtained in crystalline state. The presented findings are important for both fundamental understanding of possible formation processes and for promoting practical uses of these materials.